2001
DOI: 10.1177/0273475301233006
|View full text |Cite
|
Sign up to set email alerts
|

Student-Operated Internet Businesses: True Experiential Learning in Entrepreneurship and Retail Management

Abstract: Using the Internet, students can create and carry through to completion their own business plans, from product development to marketing and promotions to operations. As measured by student satisfaction and content analysis of student reflection papers, this new technique is an effective way to study “real-world” entrepreneurship and retail management, especially in terms of developing Internet skills. Side benefits include increased fund-raising and membership for student organizations, increased community int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 20 publications
1
93
0
1
Order By: Relevance
“…For this reason there is an increase in interactive teaching methods which encourage active self-learning and action oriented pedagogy, combined with group work and project-based learning. In this context, Pittaway and Cope (2007), highlight different teaching methods for 'entrepreneurship': action learning (Leitch and Harrison, 1999); new venture simulations (Clouse, 1990;Kelmar, 1992); technology-based simulations (Hindle, 2002;Low et al, 1994); development of actual ventures (Haines, 1988); skills-based courses (Ulijn et al, 2004); video role plays (Robertson and Collins, 2003); experiential learning (Daly, 2001); mentoring (Stewart and Knowles, 2003); design-based learning (Shane and Venkataraman, 2000); and reflective practices (Schön, 1987).Some institutions and experts have even begun to question the profile of the educator who must combine the capacity for teaching with greater professional or business experience (Comisión de las Comunidades Europeas, 2005).…”
Section: Background Higher Education and Entrepreneurshipmentioning
confidence: 99%
“…For this reason there is an increase in interactive teaching methods which encourage active self-learning and action oriented pedagogy, combined with group work and project-based learning. In this context, Pittaway and Cope (2007), highlight different teaching methods for 'entrepreneurship': action learning (Leitch and Harrison, 1999); new venture simulations (Clouse, 1990;Kelmar, 1992); technology-based simulations (Hindle, 2002;Low et al, 1994); development of actual ventures (Haines, 1988); skills-based courses (Ulijn et al, 2004); video role plays (Robertson and Collins, 2003); experiential learning (Daly, 2001); mentoring (Stewart and Knowles, 2003); design-based learning (Shane and Venkataraman, 2000); and reflective practices (Schön, 1987).Some institutions and experts have even begun to question the profile of the educator who must combine the capacity for teaching with greater professional or business experience (Comisión de las Comunidades Europeas, 2005).…”
Section: Background Higher Education and Entrepreneurshipmentioning
confidence: 99%
“…However, active engagement in an activity together with enjoyment of the experience can significantly increase both motivation and learning (Karns, 2005;Elam and Spotts, 2004). It is, perhaps, not surprising that active experiential learning approaches are increasingly being introduced into syllabi to supplement traditional teaching formats (Piercy, 2013;Karns, 2005;Daly, 2001). While studies on student satisfaction with experiential learning are varied, Piercy and Caldwell (2011) found, in a multicultural study, that students reported high levels of satisfaction with experiential learning.…”
Section: Literature Review Active and Experiential Learningmentioning
confidence: 99%
“…Here, iteration and acceptance of change becomes a more appropriate goal. Hannon et al (2005) highlight that 'traditional' learning and teaching approaches within business schools are less effective, such that 'entrepreneurial skills, knowledge and behaviour' are more likely to developed through 'co-learning', confirming Daly's (2001) analysis of satisfaction surveys and 'reflection papers', and the finding that experiential approaches enabled students to enhance the levels of finance that they were able to obtain for student societies, as well as increasing their community engagement. However, the literature appears to rely upon conceptual papers as there is still a lack of empirical studies, and some that are ostensibly empirical (for example, Hartshorn and Hannon, 2005) rely upon a single case.…”
Section: Entrepreneurship Education Approaches: Traditional Versus Exmentioning
confidence: 99%